Significantly Enhanced Electromagnetic Interference Shielding Performances of Epoxy Nanocomposites with Long-Range Aligned Lamellar Structures - Wang, Lei; Ma, Zhonglei; Qiu, Hua; Zhang, Yali; Yu, Ze; Gu, Junwei (Nano-Micro Letters, 2022)
High‑efficiency electromagnetic interference (EMI) shielding materials are of great importance for electronic equipment reliability, information security and human health. In this work, bidirectional aligned Ti3C2Tx@Fe3O4/CNF aerogels (BTFCA) were firstly assembled by bidirectional freezing and freeze-drying technique, and the BTFCA/epoxy nanocomposites with long-range aligned lamellar structures were then prepared by vacuum-assisted impregnation of epoxy resins. Benefitting from the successful construction of bidirectional aligned three-dimensional conductive networks and electromagnetic synergistic effect, when the mass fraction of Ti3C2Tx and Fe3O4 are 2.96 and 1.48 wt%, BTFCA/epoxy nanocomposites show outstanding EMI shielding effectiveness of 79 dB, about 10 times of that of blended Ti3C2Tx@Fe3O4/epoxy (8 dB) nanocomposites with the same loadings of Ti3C2Tx and Fe3O4. Meantime, the corresponding BTFCA/epoxy nanocomposites also present excellent thermal stability (Theat-resistance index of 198.7 °C) and mechanical properties (storage modulus of 9902.1 MPa, Young’s modulus of 4.51 GPa and hardness of 0.34 GPa). Our fabricated BTFCA/epoxy nanocomposites would greatly expand the applications of MXene and epoxy resins in the fields of information security, aerospace and weapon manufacturing, etc. Highlights: 1 Ti3C2Tx@Fe3O4/CNF aerogels (BTFCA)/epoxy electromagnetic interference (EMI) shielding nanocomposites with long-range aligned lamellar structures were prepared by bidirectional freezing, freeze-drying and vacuum-assisted impregnation of epoxy resins. 2 Successful construction of 3D long-range aligned lamellar structures and electromagnetic synergistic effect could significantly increase the EMI shielding effectiveness and reduce the secondary contamination. 3 BTFCA/epoxy EMI shielding nanocomposites possessed outstanding EMI shielding effectiveness of 79 dB, and also presented excellent thermal stabilities and mechanical properties.